A FOREIGN BODY IN THE LARYNX OF A ONE-YEAR-OLD CHILD: CLINICAL CASE - D. M. Mustafayev (Неотложная медицинская помощь, 2018)
The author report a clinical case of a one-year-old-child treatment with a foreign body (diode lamp) in the larynx. Despite the large size of the aspirated object and its location at the level of the glottis, the child was breathing independently. The foreign body was removed through natural airways with direct laryngoscopy, avoiding complications. This case emphasizes necessity of properly performed objective examination in children of younger age in order to reveal foreign bodies of respiratory ways.